Barriers to food intake in acute care hospitals: a report of the Canadian Malnutrition Task Force. Issue 6 (20th April 2015) - Keller, H.; Allard, J.; Vesnaver, E.; Laporte, M.; Gramlich, L.; Bernier, P.; Davidson, B.; Duerksen, D.; Jeejeebhoy, K.; Payette, H.
Abstract: Background: Poor food intake is common in acute care patients and can exacerbate or develop into malnutrition, influencing both recovery and outcome. Yet, research on barriers and how they can be alleviated is lacking. The present study aimed to (i) describe the prevalence of food intake barriers in diverse hospitals and (ii) determine whether patient, care or hospital characteristics are associated with the experience of these barriers. Methods: Patients ( n  = 890; 87%) completed a validated questionnaire on barriers to food intake, including perceptions of food quality, just before their discharge from a medical or surgical unit in each of 18 hospitals across Canada. Scores were created for barrier domains. Associations between these barriers and selected patient characteristics collected at admission or throughout the hospital stay and site characteristics were determined using bivariate analyses. Results: Common barriers were being interrupted at meals (41.8%), not being given food when a meal was missed (69.2%), not wanting ordered food (58%), loss of appetite (63.9%) and feeling too sick (42.7%) or tired (41.1%) to eat. Younger patients were more likely ( P  < 0.0001) to report being disturbed at meals (44.6%) than older patients (33.9%) and missing a meal for tests (39.0% versus 31.0%, P  < 0.05). Patients who were malnourished, women, those with more comorbidity, and those who ate <50% of the meal reported several barriers across domains. Conclusions: The present study confirms that barriers to food intake are common in acute care hospitals. This analysis also identifies that specific patient subgroups are more likely to experience food intake barriers. Because self‐reported low food intake in hospital was associated with several barriers, it is relevant to consider assessing, intervening and monitoring barriers to food intake during the hospital stay.